2021
DOI: 10.3390/ma14071697
|View full text |Cite
|
Sign up to set email alerts
|

Study on Rheological Properties of Bituminous Binders and Mixtures Containing Waste Printed Circuit Boards (PCBs) and SBR Compound Modified Bitumen

Abstract: Improper handling of waste printed circuit boards (PCBs) can cause serious pollution to the water and soil environments. In order to explore a new method of recycling waste PCBs, this study investigated the effect of PCBs and butadiene styrene rubber (SBR) on the rheological properties of neat bitumen. The dynamic shear rheological (DSR) test was used to study the effect of different PCB contents on the high-temperature rheological properties of SBR-modified bitumen. Fluorescence microscopy and Fourier-transfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In recent years, several researchers have directed their attention towards repurposing NMFs in the form of asphalt mix materials, aiming to tackle the mounting quantities of these fractions. In the field of road construction materials, a significant portion of past studies has centered around exploring the application of what is known as the 'wet process' in which the NMF is introduced as an asphalt binder modifier [6][7][8][9][10][11][12][13][14][15][16][17][18][19]. In the wet process, NMF is blended with neat asphalt binder at a precise temperature and duration, utilizing a mechanical mixing machine to induce a reaction, aiming to achieve a homogeneous asphalt binder as the desired outcome.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several researchers have directed their attention towards repurposing NMFs in the form of asphalt mix materials, aiming to tackle the mounting quantities of these fractions. In the field of road construction materials, a significant portion of past studies has centered around exploring the application of what is known as the 'wet process' in which the NMF is introduced as an asphalt binder modifier [6][7][8][9][10][11][12][13][14][15][16][17][18][19]. In the wet process, NMF is blended with neat asphalt binder at a precise temperature and duration, utilizing a mechanical mixing machine to induce a reaction, aiming to achieve a homogeneous asphalt binder as the desired outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, the researchers have searched for many feasible techniques for recycling WPCB non-metallic materials, such as chemical recycling (pyrolysis, depolymerization) and mechanical recycling. Among these techniques, the mechanical treatment of PCBs is considered to be a more straightforward and effective process, and as-obtained WPCB non-metallic powder could be further applied in construction products, modified asphalt, and polymer composites [24][25][26][27]. In particular, over the past few decades, scientists and engineers have dedicated great efforts to developing ecofriendly polymer composites by incorporating WPCB non-metals into various polymer matrixes, including thermosetting resin (e.g., epoxy resins, unsaturated polyester resin, phenolic resin, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Yu et al [20] tested modified asphalt with various PCB powder amounts; they discovered that adding PCBs improved the high-temperature performance, low-temperature performance, and temperature sensitivity of the asphalt material, but had a negative influence on the fatigue life. According to Meng et al [21], the performance test of PCBs and styrenebutadiene rubber (SBR) composite-modified bituminous mix demonstrated that PCBs may greatly increase the rutting resistance and water stability of SBR-modified bitumen at high temperatures at the specified optimum concentration. At low temperatures, the crack resistance is diminished, yet it still meets the engineering criteria.…”
Section: Introductionmentioning
confidence: 99%